A Reliable Protocol for In situ microRNAs Detection in Feeding Sites Induced by Root-Knot Nematodes - Díaz-Manzano, Fernando E.; Barcala, Marta; Engler, Gilbert; Fenoll, Carmen; de Almeida-Engler, Janice; Escobar, Carolina (Frontiers in Plant Science, 2016)
Galls induced by Meloidogyne spp. in plant roots are a complex organ formed by heterogeneous tissues; within them there are 5–8 giant cells (GCs) that root-knot nematodes use for their own nurturing. Subtle regulatory mechanisms likely mediate the massive gene repression described at early infection stages in galls, particularly in giant cells. Some of these mechanisms are mediated by microRNAs (miRNAs); hence we describe a reliable protocol to detect miRNAs abundance within the gall tissues induced by Meloidogyne spp. Some methods are available to determine the abundance of specific miRNAs in different plant parts; however, galls are complex organs formed by different tissues. Therefore, detection of miRNAs at the cellular level is particularly important to understand specific regulatory mechanisms operating within the GCs. In situ hybridization (ISH) is a classical, robust and accurate method that allows the localization of specific RNAs directly on plant tissues. We present for the first time an adapted and standardized ISH protocol to detect miRNAs in GCs induced by nematodes based on tissue embedded in paraffin and on-slide ISH of miRNAs. It can be adapted to any laboratory with no more requirements than a microtome and an optical microscope and it takes 10 days to perform once plant material has been collected. It showed to be very valuable for a quick detection of miRNAs expression pattern in tomato. We tested the protocol for miR390, as massive sequencing analysis showed that miR390 was induced at 3 dpi (days post-infection) in Arabidopsis galls and miR390 is 100% conserved between Arabidopsis and tomato. Successful localization of miR390 in tomato GCs constitutes a validation of this method that could be easily extended to other crops and/or syncytia induced by cyst nematodes. Finally, the protocol also includes guidance on troubleshooting.